Human development index and foreign direct investment: an analysis of developmental policies and economic trends in zambia - Phiri, Joseph (My University, 2019)
Zambiya hükümeti 2030 orta gelir statüsü vizyonunu gerçekleştirme arayışında, birkaçkalkınma politikası kurdu. Bunlar ekonomik büyümeyi hızlandırmak ve insani gelişmeyiiyileştirmek için mümkün kılındı. Bu tez, İnsani Gelişme endeksi ve bileşenlerine, DoğrudanYabancı Yatırım’a ve diğer ekonomik eğilimlere bakmıştır. Bunlar 1990’dan 2017 yılınakadar analiz edilmiş ve ayrıca belirli ülkelerle karşılaştırılmıştır. Zamanla söz konusugöstergelerde Zambiya için iyileşmeler oldu. Ancak, yetersiz inovasyon seviyeleri veyoksulluk seviyelerinin yavaş düşmesi gibi konularla ilgili endişeler halen mevcuttur.Ortalama eğitim süresi yedi yıl idi ve bu da ülkenin Küresel İnovasyon sıralamasında düşüksıralamada yer almasına katkıda bulundu. Çok uluslu şirketler yatırımlar getirirken esasolarak madencilik ve imalat sektörlere odaklandığı belirtildi. Eğitim ve sağlığa bu konudaönem verilmedi. Beşeri sermayeye yatırım yapmayı savunan İçsel Büyüme Modelinidesteklemek için çok uluslu şirketlerin öncelikleri gözden geçirilmelidir. Bu tez betimleyicianaliz için tümavarımlı usavurmaya başvurmuştur. Politikalar ve ekonomik eğilimler gözdengeçirildi. Mevcut ekonomik eğilimlerin iyileştirilmesi için yatırımlar refah üzerinde doğrudanetkisi olan alanlara yönlendirilmelidir. Aynı zamanda Zambiya Kalkınma Ajansı aracılığıylahükümetin, yatırımları eğitim ve sağlık gibi sosyal alanlara yönlendirmesi de gerekiyor. Sonolarak, dış yatırımın etkisinin çok daha fazla gerçekleşmesi için kurumların yönetimininiyileştirilmesi gerekiyor.

In its quest to realize vision 2030 of middle – income status, the Zambian governmentinstituted several developmental policies. These were enabled in order to accelerate economicgrowth and improve human development. This thesis looked at the Human DevelopmentIndex and its components, Foreign Direct Investment and other economic trends. These wereanalyzed from 1990 to 2017 and also compared with specific countries. Over time there wereimprovements in the said indicators for Zambia. However, concerns still existed on issuessuch as insufficient levels of innovation and the slow decline in the poverty levels. Theaverage years of schooling were seven, which also contributed to the country’s low GlobalInnovation ranking. It was noted that Multi-National corporations when bringing investmentsmainly focussed on sectors such as mining and manufacturing. Education and health receivedinsignificant attention in this regard. In support of the Endogenous Growth Model, whichadvocated for investing in human capital, the priorities of Multi-National Corporations oughtto be revisited. This thesis applied inductive reasoning to descriptive analysis. Policies andeconomic trends were reviewed. In order to improve from the current economic trends,investment should be directed towards areas which have a direct impact on welfare. Thegovernment through the Zambia Development Agency also ought to redirect investmenttowards social aspects such as education and health. Lastly, for the impact of externalinvestment to be much more realized, the management of institutions needs improvement.
Keywords: Developmental Policies; Economic Trends; Economy; Ekonomi; Ekonomik Eğilimler; Foreign Direct Investment; Investment; İnsani Gelişmişlik Endeksi; KalkınmaPolitikaları; Yabancı Doğrudan Yatırım; Yatırım; Zambia; Zambiya Human Development Index